If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(c + -3) = 3 Reorder the terms: -1(-3 + c) = 3 (-3 * -1 + c * -1) = 3 (3 + -1c) = 3 Add '-3' to each side of the equation. 3 + -3 + -1c = 3 + -3 Combine like terms: 3 + -3 = 0 0 + -1c = 3 + -3 -1c = 3 + -3 Combine like terms: 3 + -3 = 0 -1c = 0 Solving -1c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Divide each side by '-1'. c = 0 Simplifying c = 0
| 26X*26x+18x= | | 6(t+1)=24 | | -47+7x=3x+37 | | 3x^2-2(25)=20 | | 2x+2y=420 | | 42x-20(4x)+64=0 | | 2/15x30 | | 38-3x=14-7x | | X=2x-14-8 | | 7(3s+6)=315 | | 12y+60x=120 | | 3(2i+10)=78 | | r^4+2r^3+r^2= | | 5x+8=-41-2x | | 7t-2t-5t=9+13 | | 5(a-7)=50 | | 4x/15=6/5 | | 13*4-8=x | | 2+11x=-58+x | | (e+1)*4=20 | | 15700+26883-3579= | | 2r^2-2r-1= | | 7-6+15x+9x=49 | | n^2-22+120=0 | | -2s+3=-5s+24 | | 3+x-5=4+2(x-1) | | 6x+14+9=41 | | 4*cos*2*x=1 | | (-5x)(-6y)(2z)= | | x=2700+.1x | | 5+x=2x-(-3) | | 7+30x=20x+13 |